Implementation of Income Tax Article 21 (PPh 21) before and after the TER Rate and Progressive Tax Rate for Permanent Employees at PT FIF Lampung Branch - Fatmawati, Anita; Niken Kusumawardani; Kamadie Sumanda Syafis; Ratna Septiyanti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study analyzes the implementation of Income Tax Article 21 (PPh 21) before and after changes in the Average Effective Rate (TER) and Progressive Rate based on Government Regulation (PP) No. 58 of 2023 on permanent employees of PT Federal International Finance (FIFGROUP) Lampung Branch. The purpose of the study was to evaluate the conformity of the calculation and reporting of PPh 21 with the latest regulations and to identify the impact of changes in rates on employee tax obligations. The research method used a qualitative descriptive approach with primary data (interviews and observations) and secondary data (financial documents, tax regulations, and internal company reports). Comparative analysis reveals that the use of TER tends to result in higher monthly tax burdens compared to annual progressive calculations, especially in the Non-Taxable Income (PTKP) K/3 and TK/3 categories. This finding indicates the need for adjustments to the payroll system to minimize tax differences and improve the accuracy of deductions. Keywords: Article 21 Income Tax; Calculation of Article 21 Income Tax with TER and Progressive rates; PP No. 58 of 2023.